Adult Learners and Credit for Prior Learning: Analytical Thinking and Motives - Carrie J. Boden; Catherine A. Cherrstrom; Todd Sherron (Adult Education Research Conference, 2023)
This study examined 364 adult learners using linguistic inquiry and word count (LIWC) of reflective writing assignments with implications for adult learners and educators and credit for prior learning (CPL).
Keywords: adult learners; nontraditional students; credit for prior learning (CPL); prior learning assessment (PLA)